Mewaspadai Praktik Jurnalisme yang Memproduksi Keburukan - Ana Nadhya Abrar (Program Studi Ilmu Komunikasi, 2007)
Journalism could be a tool to produce news stories bombastically. Bombastic news on bad reality could produce bad things. In order not to make journalism producing bad things, we have to have some principles in reporting bad realities. The article suggests one principle: to present bad reality as the way it is. The practice of this principle is not so difficult since the fact has shown that the Indonesian press has been made public sphere on bad realities successfully. However, in practicing this principle, the joumalists still place their selves as doers inprofession and doers in media.